Assessment of Thermal Stress on Well Integrity as a Function of Size and Material Properties. (July 2017) - Roy, Pratanu; Morris, Joseph P.; Walsh, Stuart D.C.; Iyer, Jaisree; Carroll, Susan; Todorovic, Jelena; Gawel, Kamila; Torsæter, Malin
Abstract: Wellbore integrity is critical to long term carbon storage. During CO2 injection, changes in temperature may result in large stress variations that can damage the well, threatening its integrity. The different materials comprising the wellbore and near-wellbore environment (namely the casing, cement and surrounding rock) possess different thermal properties. Consequently, there can be considerable variations in both material properties and thermal gradients across these layers, resulting in different amounts of contraction and expansion of these materials. This may generate sufficient thermal stresses to lead to fracture within the cement and/or host rock, or delamination of the cement/casing or cement/rock interfaces. Downsized wellbore samples have been used in laboratory studies to investigate the failure modes and failure criteria during thermal cycling operations. However, it is not clear to what extent such results can be reliably used to predict well failure at field scale conditions. In this work, we conduct a parameter study involving the size and material properties of the wellbore samples subjected to different rates of thermal loading, with the objective of predicting how these parameters can affect the thermal stress in field scale well conditions. A state-of-the-art parallel multiscale, multiphysics code named GEOS, developed at Lawrence Livermore National Laboratory, was used to study the thermal response of wellbore materials. A finite element solver considering linear elastic materials was coupled with a finite volume heat equation solver to simulate the wellbore deformation and fracture during thermal cycling. To understand the effect of wellbore size on thermal fracturing, simulations were conducted at different height to diameter ratios. The wellbore sample size was systematically varied from the lab scale to field scale with several intermediate scales. The change in thermal stresses were compared for different scales. Additionally, the effect of elastic modulus and cooling rates were studied.